A Method for Tapering Antipsychotic Treatment That May Minimize the Risk of Relapse. (23rd March 2021) - Horowitz, Mark Abie; Jauhar, Sameer; Natesan, Sridhar; Murray, Robin M; Taylor, David
Abstract: The process of stopping antipsychotics may be causally related to relapse, potentially linked to neuroadaptations that persist after cessation, including dopaminergic hypersensitivity. Therefore, the risk of relapse on cessation of antipsychotics may be minimized by more gradual tapering. There is converging evidence that suggests that adaptations to antipsychotic exposure can persist for months or years after stopping the medication—from animal studies, observation of tardive dyskinesia in patients, and the clustering of relapses in this time period after the cessation of antipsychotics. Furthermore, PET imaging demonstrates a hyperbolic relationship between doses of antipsychotic and D2 receptor blockade. We, therefore, suggest that when antipsychotics are reduced, it should be done gradually (over months or years) and in a hyperbolic manner (to reduce D2 blockade "evenly"): ie, reducing by one quarter (or one half) of the most recent dose of antipsychotic, equivalent approximately to a reduction of 5 (or 10) percentage points of its D2 blockade, sequentially (so that reductions become smaller and smaller in size as total dose decreases), at intervals of 3–6 months, titrated to individual tolerance. Some patients may prefer to taper at 10% or less of their most recent dose each month. This process might allow underlying adaptations time to resolve, possibly reducing the risk of relapse on discontinuation. Final doses before complete cessation may need to be as small as 1/40th a therapeutic dose to prevent a large decrease in D2 blockade when stopped. This proposal should be tested in randomized controlled trials.